Plasma protein levels and hepatocellular carcinoma: a Mendelian randomization study with drug screening implications - Longhui Xie; Dekun Song; Jianwei Lan; Pengpeng Liu; Shuang Qin; Yinkuan Ning; Quanyan Liu (Discover Oncology)
Abstract Background Hepatocellular carcinoma (HCC) remains a significant cause of cancer-related mortality, highlighting the need for novel therapeutic strategies. Identifying key proteins and potential therapeutic agents is critical for improving treatment outcomes. Methods We employed Mendelian randomization to identify proteins associated with HCC risk and utilized drug enrichment and molecular docking analyses to discover potential therapeutic agents. The efficacy of identified drugs was evaluated in vitro using immune-tumor co-culture systems and in vivo in a murine HCC model. Single-cell expression profiling and clinical sample analyses were conducted to explore expression patterns. Results Our analyses identified 16 proteins linked to HCC pathogenesis. Among the therapeutic agents tested, Belinostat significantly enhanced T cell-mediated cytotoxicity against HCC cells and effectively reduced tumor growth in vivo. Single-cell analysis revealed significant modulation of immune cells within the tumor microenvironment, suggesting potential mechanisms for the observed therapeutic effects. Conclusion This study highlights the potential of Belinostat as a promising therapeutic agent for HCC. By modulating immune responses and tumor growth, Belinostat offers a novel approach to HCC treatment, warranting further clinical investigation to validate its efficacy and therapeutic potential.